Risiko Pendapatan dan Faktor yang Mempengaruhi Pendapatan Usahatani Padi Sawah Tadah Hujan (Studi Kasus di Kelurahan Sibatua Kecamatan Pangkajene Kabupaten Pangkep) - Hanisah Hanisah; Arifin Arifin; Azisah Azisah (Jurnal Agribis, 2021)
ainfed lowland rice farming is a farming that utilizes rainwater for irrigation channels on the land. Sibatua Sub-district, Pangkajene District, Pangkep Regency has an area that is mostly rainfed rice farmers for the sustainability of their farming with existing resources. The results of this study aimed to obtain the income risk and income factors of rainfed lowland rice farming. The data technique used is descriptive quantitative analysis and multiple regression to determine the risk of income from rainfed rice farming. This research was conducted in Sibatua Village, Pangkajene District, Pangkep Regency. The factors that affect the income of rainfed lowland rice farming in Sibatua Village, Pangkajene District, Pangkep Regency are fertilizer production and prices.